Development of a Model for Exploring Local Wisdom in Creative Economy Based on E-Crowdsourcing to Enhance Family Engagement in West Java, Indonesia - Ramlan Ramlan; Dini Riani; Arifin Ahmad (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
Modernization and globalization often shift the values of local wisdom that has been built, which should be able to develop family members, especially the potential of children. Children are inseparable from their parents' parenting, but currently the role of parents has shifted to fulfilling needs without paying attention to children, due to the economy in difficult conditions. So, there are problems with parenting and the economy. This condition is increasingly complex in West Java Province, which statistically faces a number of significant social challenges, including high levels of female labor force participation, high divorce rates, and high unemployment rates, especially among women and young people. The need for education for parents in managing the family, parents who join the involvement in family community programs are more objective and able to manage in a more planned parenting style. In addition, the role of non-formal education such as tutoring institutions has the opportunity to collaborate with the family community more advanced in managing the growth and development of children's potential and can form a market from the community with creative economy partnerships. Tutoring today not only manages the learning needs of children, but can also develop with the involvement of parents to learn together with programs that adapt to change. The synergy between children and parents is expected to be managed properly from the programs that should be developed. Local Wisdom of Creative Economy Assisted by E-Crowdsourced can increase family involvement in family communities in West Java Province in Indonesia.